2020
DOI: 10.1002/mgg3.1089
|View full text |Cite
|
Sign up to set email alerts
|

Novel SMAD3 p.Arg386Thr genetic variant co‐segregating with thoracic aortic aneurysm and dissection

Abstract: Background Pathogenic variants in the SMAD3 gene affecting the TGF‐β/SMAD3 signaling pathway with aortic vessel involvement cause Loeys‐Dietz syndrome 3, also known as aneurysms–osteoarthritis syndrome. Methods Description of clinical history of a family in Sweden using clinical data, DNA sequencing, bioinformatics, and pedigree analysis. Results We report a novel SMAD3 variant, initially classified as a genetic variant of uncertain clinical significance (VUS), and later found to be co‐segregating with aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…SMAD3 is also regulated by serotonin (55) which has been implicated in SUID (56). Variants in this gene have been described in patients that died of sudden cardiac death, heart failure and aortic aneurysm (57)(58)(59)(60)(61).…”
Section: Ros Pathway Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMAD3 is also regulated by serotonin (55) which has been implicated in SUID (56). Variants in this gene have been described in patients that died of sudden cardiac death, heart failure and aortic aneurysm (57)(58)(59)(60)(61).…”
Section: Ros Pathway Variantsmentioning
confidence: 99%
“…SMAD3 is also regulated by serotonin (Chen, 2014) which has been implicated in SUID (Cummings, 2019). Variants in this gene have been described in patients that died of sudden cardiac death, heart failure and aortic aneurysm (Loeys, 2018; Engström, 2020; Ou, 2020; Hanna, 2021; Humeres, 2022).…”
Section: Ros Pathway Variantsmentioning
confidence: 99%
“…Of these, exome sequencing revealed that SMAD3 mutations cause 2% of familial thoracic aortic aneurysms and dissections (TAAD) ( 67 ). As a result of the identification of fresh missense mutations in SMAD3’s evolutionarily conserved areas, Loeys-Dietz syndrome (LDS) type 3 has also been more precisely identified ( 68 , 69 ). Similarly, a nonsense variant and four missense variants in the MH2 structural domain of SMAD2 ( 70 ) and a heterozygous missense variant in the MH1 structural domain of SMAD4 were detected by sequencing in patients with sporadic thoracic aortic disease and published as first reports ( 71 ), perhaps in relation to its important role in the proliferation of vascular smooth muscle cells (VSMCs), extracellular matrix maintenance and vascular remodeling related ( 72 ).…”
Section: Discovery Of Aad Biomarkers Based On Multi-omics Technologiesmentioning
confidence: 99%
“…LDS3 is characterized by aneurysms and tortuosity of the aorta and/or middle-sized arteries, accompanied by osteoarthritis (5,6). Currently, over 60 different P/LP variants in SMAD3 have been identified in LDS3 families (24)(25)(26)(27)(28), including missense, truncating and splicing variants, and intragenic and whole gene deletions (24,29,30). Interestingly, large phenotypic variation is described between LDS3 families, suggesting that, among others, genotype and ancestry might play a role.…”
Section: Introductionmentioning
confidence: 99%